Physico-chemical properties of Seepage stream at Shripur area, eastern Nepal - Chhetry, Damodar Thapa; Pal, Joydeb (Nepalese Journal of Biosciences, 2013)
Physico-chemical parameters of the Seepage stream of Shripur area were studied for two years from July, 2002 to June, 2004, once in every month at regular intervals. The maximum air temperature was recorded in rainy season during first year (July, 2002 to June, 2003) and second year study period (July, 2003 to June, 2004). Water temperature was maximum in summer and lowest in winter season. Transparency, total alkalinity, total hardness, chloride were maximum in winter season. Free CO2 and BOD was maximum in summer season. The minimum transparency, total alkalinity, total hardness and chloride were recorded in rainy season. DO and pH were maximum in winter and minimum in summer season during the whole study period. Air temperature, water temperature, free CO2, BOD showed positive and significant correlation with each other. Transparency showed positive and significant correlation with pH, DO, total alkalinity, total hardness and chloride. pH showed positive and significant correlation with DO and chloride. Similarly, DO, total alkalinity, total hardness and chloride showed positive and significant correlation with each other. DOI: http://dx.doi.org/10.3126/njbs.v2i0.7489 Nepalese Journal of Biosciences 2 : 46-54 (2012)